P50 Predictive factors for indeterminate results in interferon-γ release assays – a problem to consider. (3rd September 2019) - Santos, JA; Duarte, R; Nunes, C
Abstract : Background: Interferon-γ release assays (IGRA) are a crucial diagnostic tool for the detection of a Mycobacterium tuberculosis infection in order to control and eliminate the tuberculosis (TB) epidemic. Indeterminate results can occur and represent a considerable problem for clinical management, since they imply the lack of clear information about the patient's TB infection status. The aim of the study was to identify risk factors that could be associated with indeterminate IGRA results. Methods: Retrospective cohort study carried out using data from the Portuguese National Tuberculosis Surveillance system, from 2008 to 2015. Were included in the study 1230 patients with active TB and an IGRA result. The IGRA test used in the patients enrolled in the study was the QuantiFERON-TB Gold In-Tube (Qiagen). The association between indeterminate IGRA results and sociodemographic factors, comorbidities and the site of disease were evaluated through bivariate and multivariate logistic regression analysis. Results: Of the 1230 patients reported with active TB in the SVIG-TB database (2008–2015) that underwent an IGRA test, 857 patients (69.7%) had a positive test result, 212 (17.2%) had a negative result and 161 (13.1%) had an indeterminate result. Majority of the patients with indeterminate results were male (67.7%) and more than half had more than 50 years (57.1%). The proportion of indeterminate results increased as the age increased, with patients over 80 years old presenting the highest proportion of indeterminate results. Age ≥ 65 years (OR 2.51, p<0.001), alcohol abuse (OR 3.04, p=0.001) and pulmonary TB (OR 3.07, p<0.001) were predictive factors for indeterminate IGRA results. Conclusion: Age ≥ 65 years, alcohol abuse and pulmonary TB were identified as factors for the occurrence of indeterminate IGRA results. The first two factors can be identified prior to the test and thus help to quickly identify the probable cause of an indeterminate outcome and lead to the use of other clinical and diagnostic means to detect a possible infection.